Integration of Study Courses as Means of Modernization of Tertiary Education - Stankovic, Sladjana S.; Golubović-Ilić, Irena B. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
The university teaching in which the approach to the acquisition of the content is integrated, while simultaneously achieving the correlation of two study courses, is more dynamic, intellectually more valuable, and emotionally richer than the usual, traditional teaching. The paper highlights the importance and advantages of implementing an integrated approach and correlation in working with students training for teaching in preschool institutions. A realization of a class was given as an example during which the content from both the Physical Education Methodology and the Environmental Study Methodology was observed, the principle of rationalization and economy was applied. As a result, the students noticed the interconnectedness between the subjects, gained experience, and saw a number of practical examples that can be applied in kindergartens in their future work. Common, mutually related elements or parts of the content of the Physical Education Methodology and the Environmental Study Methodology, at first, were difficult to notice. For this reason, the integration and combining of contents of these two study courses represented a challenge and a space in which we can express our originality and creative ideas.
Keywords: university teaching; integrated approach; correlation; Physical Education Methodology; Methodology of getting to know the environment